The lifestyle and behavioural risk factors of future doctors in Universiti Teknologi MARA, Malaysia / Xin-wee Chen and Zaliha Ismail. - Chen, Xin-wee Chen; Ismail, Zaliha Ismail (Universiti Teknologi MARA Cawangan Selangor, 2018)
Lifestyle and behavioural risk factors in middle-aged adults are proven to have an impact on later-life outcomes; hence health promotion activities should aim at the population before they reach their mid-life. Medical students will be representing a community in promoting health, henceforth they should have a healthy lifestyle and behaviour in order to facilitate and adoption of preventive practices in their future life as physicians. Therefore, this study was aimed to determine the lifestyle and behavioural risk factors among future doctors in a public university in Malaysia. Methods: A cross-sectional study was conducted at the Faculty of Medicine, Universiti Teknologi MARA (Sungai Buloh Campus). Simple random sampling was used to select eligible subjects among undergraduate medical students (pre-clinical years). A self-administered pro forma checklist was given to the subjects who consented. Descriptive analysis was performed, and univariate analysis was done by Chi-square, Fisher’s Exact test and independent t-test. Results: A total of 252 subjects participated. The majority (96.8%) were of Malay ethnicity and three-quarter of the subjects were females (76.2%). A small number of subjects were smokers (2.4%) and alcoholic consumers (1.2%). Approximately half (57.3%) of the female subjects had normal body mass indices, while this was only seen in one-third (35.0%) of male subjects. Most subjects (72.2%) exercised at least once a week, however only 17.1% of the subjects exercised at the recommended levels. There was a significantly higher proportion of males who had adequate exercise compared to that of females. Conclusion: Inadequate physical activity and imperfect BMI of the study subjects warrant exclusive promotion and education of healthy lifestyle in this population. It would probably be beneficial if assessment of lifestyle and behavioural risk factors could be conducted before these subjects embark into their professional working life.